PEMBERDAYAAN PEREMPUAN MELALUI INDUSTRI RUMAHAN DAN HOMESTAY UNTUK MENDUKUNG PENGEMBANGAN DESA WISATA: STUDI KASUS DESA SAKERTA TIMUR, KUNINGAN, JAWA BARAT - Tessina Liliani Nurtanio; Himawan Brahmantyo (Universitas Merdeka Malang, 2021)
Tourism village has become more popular in the past recent years due to the transition of traveler’s interest from urban to rural tourism. Sakerta Timur is one of the villages that want to become the pioneer of tourism villages in Kuningan Regency. One of the main supporters of the tourism industry is human resources, including women. Traditional gender roles, assign women the main responsibilities for raising children and doing household work, but in Sakerta Timur, most of the women help the husband’s role in improving the household economy. The women have the ability to process local foodstuffs for sale since these local products have been able to contribute to village income. Home industry and homestay in Sakerta Timur are mostly managed by women which is half of the population. They are very potential to support the development of their village to become a rural destination through the home industry and homestay, but there is still a lack of support from the village government due to physical development priority. Using in-depth interviews, observation, and other supplemental evidence, this study was to analyze the potential and how to empower women in Sakerta Timur to support their village to become rural tourism destination through home industry and homestay, since these two industries are the key factors of tourism. The findings from this paper hopefully will help another potential tourism village how to develop their village to become a rural tourism destination through the food home industry and homestay which were managed by women.